Determinants of The Unemployment University Graduates in Java Island - Kinasih, Putri Suri; Nihayah, Dyah Maya (Efficient: Indonesian Journal of Development Economics, 2022)
This study aims to analyze the effect of the Provincial Minimum Wage, Economic Growth, Foreign Investment, and Inflation on the educated unemployment of university graduates in Java. This study uses a quantitative method with panel data from 6 provinces in Java and in the 2010-2020 period. The test in this study uses the Fixed Effect regression analysis method with the Ordinary Least Square (OLS) method. The result of this research is that the variable of economic growth has a significant effect on the impact of educated university graduates on the island of Java, while the variables of the provincial minimum wage, foreign investment, and inflation have no significant effect. Suggestions from the results of this study are that the government and companies pay more attention to the welfare of the community and their employees. The government can maintain the stability of economic growth and pay more attention to macro policies related to economic growth. The government can optimize the role of established foreign investment in Indonesia to be able to absorb more workers and make regulations that encourage companies to be more productive so as to increase production output. Penelitian ini bertujuan untuk menganalisis pengaruh Upah Minimum Provinsi, Pertumbuhan Ekonomi, Penanaman Modal Asing, dan Inflasi terhadap pengangguran terdidik lulusan universitas di Jawa. Penelitian ini menggunakan metode kuantitatif dengan data panel dari 6 provinsi di Jawa dan pada periode 2010-2020. Pengujian dalam penelitian ini menggunakan metode analisis regresi Fixed Effect dengan metode Ordinary Least Square (OLS). Hasil penelitian ini adalah variabel pertumbuhan ekonomi berpengaruh signifikan terhadap dampak lulusan perguruan tinggi terdidik di pulau Jawa, sedangkan variabel upah minimum provinsi, penanaman modal asing, dan inflasi tidak berpengaruh signifikan. Saran dari hasil penelitian ini adalah pemerintah dan perusahaan lebih memperhatikan kesejahteraan masyarakat dan karyawannya. Pemerintah dapat menjaga stabilitas pertumbuhan ekonomi dan lebih memperhatikan kebijakan makro terkait pertumbuhan ekonomi. Pemerintah dapat mengoptimalkan peran penanaman modal asing yang sudah mapan di Indonesia agar mampu menyerap lebih banyak tenaga kerja serta membuat regulasi yang mendorong perusahaan untuk lebih produktif sehingga dapat meningkatkan output produksi.